Importált és hazai valóság - Botos, Katalin (Közép-Európai Közlemények, 2009)
In the world there is a Great Depression II. as a result of many factors First: The profit seeking financial intermediaries were too greedy. Second: there was a revolution of unlimited expectations (Aurelio Peccei) among the people in the developed world. Too quickly, too many people wanted to enlarge their possessions (Housing investments). Third: Big Tigers, India, China and the oil countries had fuelled the world liquidity and it pushed down the interests. In Hungary the population cannot be blamed for the quick growing of the foreign exchange indebtedness of the country. The Hungarians had to wait 12–14 years to get back after a long transformation recession in the 1990ies to the same level as they had been before the political changes. The blame for the situation falls upon the latest ruling government. It has forced an export led growth, a privatisation on too many fields and did not control public expenditures. As a result we have now a too concentrated and vulnerable export sector, a privatised infrastructure with a pressure on the forint exchange rates, and a high state indebtedness. We couldn’t introduce the euro and our currency is in danger of devaluation. Now we are absolute dependent from the help of the IMF because of the lack of confidence of the financial markets.